O Rio Grande do Sul dividido : conflitos políticos eleitorais entre pessedistas e petebistas para o governo estadual - Asturian, Marcos Jovino (Universidade do Vale do Rio dos Sinos, 2019)
This thesis aims to analyze the electoral dispute between the Partido Social Democrático (PSD) and Partido Trabalhista Brasileiro (PTB) in the 1947, 1950 and 1954 elections for governor of Rio Grande do Sul. Therefore, will be used elements of the political field theory, developed by French sociologist Pierre Bourdieu, as an instrument of thought for the understanding of conflicts in election campaigns. The pessedistas and trabalhistas produced narratives – force-ideas – that were disclosed – by means of paid materials – in written press, whose objective consisted in the construction of representations about the reality of Rio Grande do Sul, its problems and ways of solution, as well as referrals. Thus, the guiding thread of the thesis is the conflicting relational logic, in other words, the game of oppositions and distinctions between parties and candidates. It is believed that a more focused analysis of electoral conflicts can contribute and increase the understanding about the political dynamics of this period. The sources used in this work were the Correio do Povo and Diário de Notícias newspapers, as well as in the annals of sul-rio-grandense Legislative Assembly.
Keywords: Rio Grande do Sul; Disputa Eleitoral; Partido Social Democrático; Partido Trabalhista Brasileiro; Rio Grande do Sul; Electoral Dispute; Partido Social Democrático; Partido Trabalhista Brasileiro; ACCNPQ::Ciências Humanas::História